Effectiveness of Monetary Policy in Indonesia - Pasaribu, Esti; Ekaputri, Retno Agustina; Yefriza, Yefriza (Integrated Journal of Business and Economics (IJBE), 2023)
This research investigated the effectiveness of the monetary policy in Indonesia. A cumulative summary test was used to determine the response of economic growth to monetary policy between 1990-2020. Furthermore, the data on gross national income, money supply, inflation, exchange rate, and interest rate was processed using error correction model regression. The results showed that monetary policy improved economic growth through channels of inflation and money supply, and the correlation was strong and valid both in the short and long term. The correlation of exchange rate and interest rate to economic growth was also observed to be significant only in the long term. The four variables had a significant, simultaneous effect on Indonesia's GDP. Therefore, the government needs to pay special attention to the enactment of monetary policy.